Treatment of water for human supply: contributions of Six Sigma methodology - Mazieiro Pohlmann, Paulo Henrique; Francisco, Amanda Alcaide; Ferreira, Marco Antonio; Chiappetta Jabbour, Charbel Jose [UNESP] (Assoc Brasileira Engenharia Sanitaria Ambiental, 2015)
The Six Sigma methodology is a business strategy based on making an objective decision, considering real and meaningful data for the creation of viable targets, analyzing the defects' cause and suggesting ways to eliminate the gap between the performance process and the desired goal. Through the verification of the importance of integration between the environmental sanitation and the management operations, it was attempted to, through a simulation, perform an analysis of the processes involved in conventional water treatment from the perspective of Six Sigma methodology. Considering a production of 2.58 million m(3).month(-1) and a 3.0 Sigma level, the nonconforming volume would be 173.1 m(3).month(-1). If the Six Sigma excellence level could be reached, the nonconforming volume would be 7.75 m(3).month(-1).
Keywords: Six Sigma; environmental sanitation; Water Treatment Plant